2018
DOI: 10.1183/13993003.00122-2018
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of primary cilia in COPD

Abstract: Chronic obstructive pulmonary disease (COPD) is a major economic and social concern worldwide because of its impact on mortality and morbidity [1]. COPD is characterised by airway epithelium remodelling, a hallmark of dysregulated airway epithelium plasticity [2]. There are currently no available therapeutics to restore the integrity and functionality of the epithelium. Therefore, novel sources of investigation are becoming crucial to understand the alterations at the root of COPD initiation. Non-motile primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 15 publications
2
28
0
Order By: Relevance
“…Alterations of the presence, structure and function of cilia on differentiated AEC were not completely elucidated while the mucociliary clearance was often seen as a readout of normal lung function [70,71]. Mucins secretion was not significantly impacted although there was a trend favouring Muc5b producing cells despite the reduction of MUC5AC and MUC5B transcripts at the beginning of differentiation, therefore it will be interesting to fully characterize cilia and goblet cells alterations upon HH inhibition to understand the molecular events leading to epithelial remodelling particularly since we also observed primary cilia defects in COPD patients [50].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Alterations of the presence, structure and function of cilia on differentiated AEC were not completely elucidated while the mucociliary clearance was often seen as a readout of normal lung function [70,71]. Mucins secretion was not significantly impacted although there was a trend favouring Muc5b producing cells despite the reduction of MUC5AC and MUC5B transcripts at the beginning of differentiation, therefore it will be interesting to fully characterize cilia and goblet cells alterations upon HH inhibition to understand the molecular events leading to epithelial remodelling particularly since we also observed primary cilia defects in COPD patients [50].…”
Section: Discussionmentioning
confidence: 95%
“…Immunohistochemistry was performed on formalin-fixed paraffin-embedded (FFPE) lung tissues distant from the tumour as previously described [50] and frozen tissues. Five 5 μm sections were processed for H&E staining and observed on microscope (x20) to confirm the presence of bronchi.…”
Section: Methodsmentioning
confidence: 99%
“…[ 79,80,119 ] These are used to study levels of inflammatory markers and immune cell activity, which may also form the basis for patient stratification and treatment. It is also possible to study markers of mucociliary clearance, such as levels of ciliary metaplasia [ 80,120 ] and ciliary beat frequency, [ 79 ] the reduction of which may increase patient vulnerability to infection and sputum production. An altered respiratory microbiota is also implicated in COPD pathophysiology, [ 121 ] with acute exacerbations linked to microbial–pathogen interactions and infection.…”
Section: Modelling the Respiratory System In Vitromentioning
confidence: 99%
“…Recently, Perotin et al . showed that primary cilia (non-motile) are dysregulated in COPD patients both in remodelled and non-remodelled epithelium 9 . More broadly, ciliopathies are particularly prone to induce cystic diseases at various sites, notably the lung in primary ciliary dyskinesia (bronchiectasis) or the kidneys (in polycystic kidney disease) 10,11 .…”
Section: Introductionmentioning
confidence: 99%